L. V. SHYTYK: STRUCTURE OF NICKNAMES IN SOCIAL NETWORKS - SHYTYK, L. V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. The specific nature of Internet discourse predicts a change in certain provisions of linguistics and a special form of information presentation. In view of this, there is a need for a comprehensive study of nicknames as a special type of presentation of the participant of communication. The relevance of the study is due to the need to generalize and systematize the existing scientific experience of studying the structure of nicknames in social networks and to characterize their specifics. Purpose. The purpose of the article is a comprehensive analysis of the structure of nicknames in social networks. Results. The peculiarities of the structure of nicknames collected by means of questionnaires of students and pupils are investigated. Monocomponent and multicomponent names are distinguished according to the peculiarities of structural components. Monocomponent nicknames are analyzed by complicating (additional) components and by the method of graphic transmission. Multicomponent onyms are grouped according to the peculiarities of writing, the method of creation and the number of components, the specifics of graphic transmission, the types of punctuation and their purpose. Among the multi-component names there are network names that do not contain numbers (by method of formation and number of components), in the structure of which there are numbers (by method of formation and number of components, by location of the number relative to the word and by number of numbers). Originality. The available scientific experience of studying the structure of nicknames in social networks is generalized and systematized and the specifics of onyms selected by the method of questionnaires of students are analyzed. Conclusions. The study of the structural features of nicknames made it possible to distinguish between monocomponent and multicomponent network names. The most common subgroups of monocomponent names are the nouns complicated by additional vowels (40 %) and nicknames containing uppercase or lowercase letters or their combinations, as well as non-normative signs and symbols (65 %). Among multicomponent network names the productive nicknames are the intermediate ones between spelling together and separately (67 %), nicknames formed by a combination of two words (83 %), names that contain numbers (51 %), nicknames that combine lowercase letters, punctuation signs and / or indents (without numbers) (40 %), nouns with underscores (40 %). We see the prospect for further scientific research in the comprehensive study of the structure, semantics, pragmatics of nicknames in social networks.